Identifying Students’ Metacognitive Characteristics in Solving Problems on the Hydrocarbons Topic - Miterianifa, Miterianifa; Utari, Lidya; Yasthophi, Arif; Yanda, Sri Novita (Jurnal Tadris Kimiya, 2025)
Metacognitive abilities play a critical role in students’ learning processes by enabling them to regulate their thinking and select effective learning strategies. Understanding one’s own metacognition allows students to optimize their learning outcomes by adapting approaches that align with their cognitive strengths. This study aimed to identify the metacognitive characteristics and levels of Grade XI students in learning hydrocarbons during the 2023/2024 academic year at MAN 4 Kampar. A quantitative descriptive research design was employed, involving 13 purposively selected students. Data were collected using an essay-based test instrument designed to assess three metacognitive indicators: declarative, procedural, and conditional knowledge. The results revealed that students demonstrated a high level of declarative knowledge (92.40%, categorized as very good), but performed poorly on procedural (60.26%) and conditional (59.62%) indicators, both falling into the low category. These findings suggest that while students possess strong factual knowledge, they struggle with applying and adapting that knowledge in problem-solving contexts. The study highlights the need for instructional strategies that explicitly develop procedural and conditional metacognitive skills to support deeper and more autonomous learning in chemistry education.